GE_GERICHTE PM/84/2020 vom 30. März 2020 - GE Cour de justice (2020)
MESURE THÉRAPEUTIQUE INSTITUTIONNELLE;LIBÉRATION CONDITIONNELLE;EXPERTISE PSYCHIATRIQUE | CP.56; CP.56.al6; cp.59; cp.62.letc; CP.64